Influence of Nb-doping on the structural and electrical properties of lanthanum molybdates, La5.4MoO11.1 - López Vergara, Adrián; Porras-Vázquez, José Manuel; Vollestad, Einar; Canales-Vázquez, J.; Ramírez-Losilla, Enrique; Marrero-López, David (My University, 2018)
Nowadays, hydrogen is receiving a great deal of attention as an energy carrier. Commonly, it is obtained by hydrocarbons reforming, such as natural gas, coal and biomass. However, the resulting hydrogen needs to be purified to remove by-products and impurities, increasing the production costs. An alternative for hydrogen production is proton-conducting ceramics, where hydrogen separation takes place via a chemical potential gradient across the membrane.1, 2 In this work, Nb-doped La6MoO12--based compounds have been investigated as part of a new family of materials very competitive as SOFC electrolyte and hydrogen separation membranes.3 These materials, La5.4Mo1-xNbxO11.1-x/2 (x = 0.05, 0.10, 0.15 y 0.20) were synthesized by the freeze-drying precursor method and calcination conditions have been optimized to obtain single phases. A complete characterization has been carried out using X-Ray powder diffraction and scanning and transmission electron microscopy. The total conductivity was determined by complex impedance spectroscopy at different atmospheres. Different polymorphs are obtained as a function of the cooling rate and the dopant amount. The samples cooled by quenching are cubic with a fluorite-type structure (Fm3 ̅m) and the ones cooled at 50 y 0.5 ºC•min-1 are rhombohedral (R1 and R2 polymorphs). For niobium contents higher than x = 0.10 the R1 polymorph is stabilised at cooling rates equal or inferior to 50 ºC•min-1. For all three series, the incorporation of niobium into La5.4MoO11.1 increases the conductivity, reaching the best values for x=0.10 and the sample obtained by quenching.
Keywords: Lantánidos; Lanthanum molibdates; Hydrogen separation membranes; Nb doping; Polymorphism